Solid electron acceptor effect on biocatalyst activity in treating azo dye based wastewater. Issue 116 (6th November 2015) - Sreelatha, S.; Velvizhi, G.; Reddy, C. Nagendranatha; Modestra, J. Annie; Mohan, S. Venkata
Abstract : Schematic representation of (a) BET, (b) AnT and (c) abiotic-control operations along with the electron flux mechanism occurring in presence and absence of electrode assembly. Abstract : The functional activity of anaerobic bacteria in the presence of an electrode as solid electron acceptor was comprehensively evaluated during the treatment of azo dye based wastewater. The experiments were performed in three different reactor setups, viz., bio-electrochemical treatment (BET; with electrode assembly and anaerobic biocatalyst), anaerobic treatment (AnT; with anaerobic biocatalyst and absence of electrode assembly) and abiotic reactor (control; with electrode assembly and absence of anaerobic biocatalyst) with 50 mg l −1 azo dye concentration. Maximum dye removal was observed with BET (69.9%) followed by AnT (42%) and control (2.4%). The bioelectrogenic performance was observed to be higher in BET (92.1 mW m −2 ) in comparison to abiotic-control (0.41 mW m −2 ), which is attributed to the significant influence of bacteria as biocatalyst in concurrence with the function of the electrode as solid electron acceptor in BET. The study also documented electron acceptor dependent respiration, exemplifying the influence of conjunction between electrode and bacteria on dye degradation. Two possible electron transfer mechanisms, viz., direct electron transfer (DET) through the membrane bound cytochromes to the solid electron acceptor and mediated electron transfer (MET) through reduced dye intermediates as electron shuttles, were observed during BET operation. However, AnT and abiotic control operation resulted in less and no dye breakdown, respectively, due to the lack of conjunction between the biocatalyst and electrode. The study provides a new insight into the electron acceptor dependent respiration wherein the electrode serving as a solid electron acceptor enables efficient function of anode respiring bacteria (ARB) in terms of electron flux towards dye degradation and electrogenesis.